2017
DOI: 10.26877/bioma.v6i2.1716
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH DOSIS PUPUK NPK MAJEMUK DAN PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) TERHADAP BOBOT BASAH DAN KADAR KLOROFIL DAUN TANAMAN PAKCOY (Brassica rapa L.)

Abstract: Plant Growth Promoting Rhizobacteria (PGPR) is a group of beneficial soil microorganisms for soil fertility and crops. This study aims to show the effect of PGPR supplementation in the dose of NPK fertilizer on fresh weight and leaf chlorophyll content of pakchoy (Brassica rapa L.). There ere five treatment levels, consist of variation of NPK dosage and PGPR, namely: NPK 100% (A0P0), NPK 75% + PGPR 25% (A1P1), NPK 50% + PGPR 50% (A2P2), NPK 25% + PGPR 75% (A3P3), 100% PGPR (A4P4). Each treatment was repeated 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…Nitrogen was needed as an energy source in the photosynthesis process. The increase in chlorophyll content was caused by the diversion of the reaction of the precursor compound geranylgeranyl pyrophosphate 19 . Plant height observation carried out at 8 WAP showed that there was no interaction effect between pruning, cytokinin and nitrogen application Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen was needed as an energy source in the photosynthesis process. The increase in chlorophyll content was caused by the diversion of the reaction of the precursor compound geranylgeranyl pyrophosphate 19 . Plant height observation carried out at 8 WAP showed that there was no interaction effect between pruning, cytokinin and nitrogen application Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Pemberian bakteri diazotrof tidak berpengaruh nyata terhadap rasio akar tajuk padi, diduga akibat cekaman salinitas mempengaruhi pertumbuhan akar dan tajuk. Tingginya rasio akar tajuk mengindikasi bahwa pertumbuhan akar pada kondisi salin akan lebih digalakkan dibandingkan pertumbuhan tajuk sebagai mekanisme pertahanan dengan mengurangi laju penyerapan garam (Ikhsanti et al, 2018) Aplikasi PGPR dapat meningkatkan kandungan klorofil daun melalui peranannya dalam meningkatkan serapan nutrisi melalui proses fiksasi nitrogen (Rosyida & Nugroho, 2017).…”
Section: Rasio Akar Tajukunclassified
“…Salah satu peran PGPR sebagai biofertilizer yang menyediakan nutrisi bagi tanaman, khususnya nitrogen dan fosfor. Kandungan nitrogen tanaman dapat berpengaruh terhadap fotosintesis baik lewat kandungan klorofil maupun enzim fotosintetik, sehingga meningkatkan fotosintat (bobot) yang terbentuk (Rosyida and Nugroho, 2017). Menurut Amelia et al (2017), pemberian kombinasi pupuk hara mikro cair dengan pupuk NPK memberikan pengaruh nyata terhadap hasil panen jagung.…”
Section: Hasil Panenunclassified